How Self-Construals Affect Responses to Anthropomorphic Brands, With a Focus on the Three-Factor Relationship Between the Brand, the Gift-Giver and the Recipient - Lin, Chien-Huang; Huang, Yidan (Frontiers in Psychology, 2018)
The universal mantra, “The customer is our king,” has led to considerable focus on the servant-anthropomorphized brand. However, does your “king” want to be served as a “king”? This research aims to examine how anthropomorphic brand role, self-construals and consumer responses to brands interact. In this study, four sequential experiments show that consumers with an interdependent self-construal are likely to respond more favorably toward anthropomorphic brands playing superior ‘master’ roles than toward those playing subordinate ‘servant’ roles. Here we distinguish between two types of superior role (master and mentor) based on behavior and communications. We also explore the underlying psychological mechanism of followership, as demonstrated through blind followership of someone in a master role and rational followership of someone in a mentor role. Additionally, when a third-party (recipient) is involved in the relationship between a consumer and a brand, the giver–recipient relationship moderates the relationship between an anthropomorphised brand role and self-construals.